Dissemination Strategy for Strengthening Tolerance of the Gusdurian Community of Banyumas - Luciana Devi Suryaningsih; Nana Sutikna; S Bekti Istiyanto (al-fikrah: Jurnal Manajemen Pendidikan, 2023)
In order to change the mindset and build public awareness in tolerance, there needs to be a real movement from GUSDURian Banyumas. Seeing that Banyumas is an area with diverse religious and cultural differences. In order to attract the attention of the community, GUSDURian Banyumas has taken several ways to give a message to minority groups that GUSDURian is present as the community they need. This research aims to find out how the tolerance dissemination strategy carried out by GUSDURian to the Banyumas community. The research method used by the researcher is descriptive qualitative method. The data in this study were generated through participatory observation, interviews, and documentation. The informants in this study amounted to three people, namely the Banyumas GUSDURian Coordinator, and two Banyumas GUSDURian activists. Determination of informants in this study through snowball sampling. The results of this study explain that there is a realization of the implementation of interfaith activities as a form of dissemination strategy to strengthen tolerance that has been implemented and successfully involves community participation, namely: 1) GUSDURian 17an Forum 2) Commemoration of the Great Day 3) GUSDUR Thought Class, while for internal dissemination in addition to these three points, it is added with a social media campaign for internal members of GUSDURian Banyumas. The effect of these activities is that some communities that feel marginalized begin to show themselves and join the GUSDURian community, and people from various circles, students, and residents of the surrounding environment apply an attitude of caring for each other and mutual tolerance